Lived Experiences of Undergraduate Students Failing in Mathematics Examinations: A Phenomenological Study - Lamsal, Arjun (Academic Journal of Mathematics Education, 2025)
This study explored the experiences of undergraduate students who failed mathematics examinations using a phenomenological approach. Seven participants took part in in-depth interviews, providing rich narratives of their emotional responses, social interactions, and coping strategies. Thematic analysis identified seven key themes, revealing mathematics failure as a multifaceted experience marked by anxiety, shame, and diminished self-confidence, often reinforced by social comparisons and institutional practices. Simultaneously, students demonstrated resilience, reflection, and persistence. Findings highlight that mathematics failure is not merely an academic deficit but a transformative experience that can promote self-awareness and growth when supported appropriately. The study emphasizes the importance of equitable pedagogical and instructional strategies that acknowledge students’ diverse experiences and provide constructive pathways for improvement.